Immediate impacts of COVID-19 pandemic on bean value chain in selected countries in sub-Saharan Africa - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2024)
Immediate impacts of COVID-19 pandemic on bean value chain in selected countries in sub-Saharan Africa.